PENGEMBANGAN KOSAKATA BAHASA BALI PADA USIA DINI (Usia 4-5 Tahun) - Ida Ayu Iran Adhiti; Gede Sidi Artajaya; Ida Ayu Pristina Pidada (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2022)
The development of language skills, especially the development of Balinese vocabulary for early childhood, aims to enable children to communicate verbally with their environment. The development of Balinese vocabulary at an early age that is implanted is the vocabulary of Alus or Kruna Alus. Balinese vocabulary that is classified as Kruna Alus is vocabulary that has a subtle sense of value or is respectful of respectable groups, depending on the social status of the interlocutor and the things being discussed. Basic vocabulary in Balinese developed by early childhood involves: kinship terms, names of body parts, pronouns, basic numerals, main verbs, basic state words, and universal objects. The basic vocabulary is taught to children for language teaching. The study of the development of Balinese vocabulary is presented in a qualitative descriptive manner. Data were collected from several sources as a reference library. Vocabulary teaching has a very important role in improving children's understanding and communication. The more vocabulary they have, the greater the opportunity for children to learn a language. Children are expected to be able to acquire large amounts of new vocabulary and understand and understand the meaning of the vocabulary so that they are able to use them properly and correctly. Language development methods, especially vocabulary in early childhood, are: storytelling method, conversing method, question and answer method, and role playing method.